Literature and Identity: Representing Subalterns and Hybrid Cultures in the Work of Indonesian Writers - Afrika, Ayu (Professorline, 2024)
This article examines the relationship between literature and identity, especially in the context of the subcultures and hybrids that colour the works of Indonesian writers. The author uses postcolonial theory and cultural studies approaches to analyze how Indonesian writers represent their experiences, values ​​and views as part of a marginalized and mixed society. This article also highlights Indonesian writers' challenges and contributions to developing national and global literature. Some examples of literary works discussed in this article include novels by Pramoedya Ananta Toer, Ayu Utam, Andrea Hirata, and Eka Kurniawan.